Induction of Peptide Bond Dipoles Drives Cooperative Helix Formation in the (AAQAA)(3) Peptide - Huang, Jing (The Biophysical Society, 2014)
Cooperativity is a central feature in the formation of secondary structures in proteins. However, the driving forces behind this cooperativity are poorly understood. The present work shows that the cooperativity of helix formation in the acetyl-(AAQAA)(3)-NH(2) peptide is significantly enhanced using an empirical force field that explicitly includes the treatment of electronic polarizability. Polarizable simulations yield helical content consistent with experimental measurements and indicate that the dependence of helical content on temperature is improved over additive models, though further sampling is required to fully validate this conclusion. Cooperativity is indicated by the peptide sampling either the coiled state or long helices with relatively low populations of short helices. The cooperativity is shown to be associated with enhanced dipole moments of the peptide backbone upon helix formation. These results indicate the polarizable force field to more accurately model peptide-folding cooperativity based on its physically realistic treatment of electronic polarizability.